Identification of Potential Protein Targets in Extracellular Vesicles Isolated from Chemotherapy-Treated Ovarian Cancer Cells - Chia-Yi Chan; Yi-Chun Ni; Hieu Duc Nguyen; Yung-Fu Wu; Kuen-Haur Lee (Current Issues in Molecular Biology, 2023)
Despite the ongoing clinical trials and the introduction of novel treatments over the past few decades, ovarian cancer remains one of the most fatal malignancies in women worldwide. Platinum- and paclitaxel-based chemotherapy is effective in treating the majority of patients with ovarian cancer. However, more than 70% of patients experience recurrence and eventually develop chemoresistance. To improve clinical outcomes in patients with ovarian cancer, novel technologies must be developed for identifying molecular alterations following drug-based treatment of ovarian cancer. Recently, extracellular vesicles (EVs) have gained prominence as the mediators of tumor progression. In this study, we used mass spectrometry to identify the changes in EV protein signatures due to different chemotherapeutic agents used for treating ovarian cancer. By examining these alterations, we identified the specific protein induction patterns of cisplatin alone, paclitaxel alone, and a combination of cisplatin and paclitaxel. Specifically, we found that drug sensitivity was correlated with the expression levels of ANXA5, CD81, and RAB5C in patients receiving cisplatin with paclitaxel. Our findings suggest that chemotherapy-induced changes in EV protein signatures are crucial for the progression of ovarian cancer.